Review of the Books of Persian Literature in the High School of the Old System and the Second Medium of the New System - Soltani, Majid (2020)
Many educators believe that the intellectual, national, cultural, religious, and literary foundations of each generation are laid in childhood and adolescence. An important part of this is the responsibility of each country's education system. Textbooks are one of the most important tools in this formation. Persian books are a means of narrating human thoughts and imaginations due to their attention to fiction. The present article is a research on the books of Persian literature of the old educational system and Persian of the new educational system. In this study, we intend to examine the books of Persian language and literature of the old system and the Persian books of the second secondary school in the new educational system. Classical literature, contemporary literature, poetic, prose and fusion literature, Iranian and world literature are some of the components that are examined in this research. The authors appear to have focused on the text in older books and to pay more attention to self-examination in new books. This indicates that the new books emphasize greater student engagement.